2021
DOI: 10.1002/ecs2.3421
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in habitat selection for a Neotropical migratory songbird using high‐resolution GPS tracking

Abstract: Seasonal variation in habitat selection for a Neotropical migratory songbird using high-resolution GPS tracking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 68 publications
1
20
0
2
Order By: Relevance
“…Advances in electronic tracking technologies have revolutionized our ability to monitor animal movements and behavior over extended periods of time in both terrestrial and aquatic environments. The use of radio, satellite, global positioning system (GPS), and acoustic tracking devices has expanded research on fundamental ecological topics, such as habitat requirements, dispersal, migratory routes, foraging, and home‐range characteristics (McIntyre et al, 2017 ; Powell et al, 2016 ; Séchaud et al, 2021 ; Snijders et al, 2014 ; Stanley et al, 2021 ). Each technology has strengths and limitations, and trade‐offs exist for current tracking systems depending on research questions and study species (Bridge et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in electronic tracking technologies have revolutionized our ability to monitor animal movements and behavior over extended periods of time in both terrestrial and aquatic environments. The use of radio, satellite, global positioning system (GPS), and acoustic tracking devices has expanded research on fundamental ecological topics, such as habitat requirements, dispersal, migratory routes, foraging, and home‐range characteristics (McIntyre et al, 2017 ; Powell et al, 2016 ; Séchaud et al, 2021 ; Snijders et al, 2014 ; Stanley et al, 2021 ). Each technology has strengths and limitations, and trade‐offs exist for current tracking systems depending on research questions and study species (Bridge et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Home range size and habitat selection patterns often vary during the annual cycle (Rühmann et al, 2019 ; Stanley et al, 2021 ; Wiktander et al, 2001 ). We found that the smallest (7.58 ha) and the largest (29.09 ha) home range size corresponded to an egg‐laying bird (JP4645; Tables 1 and 2 ) and a chick‐rearing bird (KGSK2033), which is consistent with general expectations for birds (e.g., Kolts & McRae, 2017 ; Zurell et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…for a wide range of genera across a diversity of heterogeneous ecosystems (e.g., Fleming et al, 1987;Van Schaik et al, 1993;Pape and Löffler, 2015;Vélez et al, 2017;Stanley et al, 2021), including chimpanzees in forest-woodland mosaic environments (Collins and McGrew, 1988;Pennec et al, 2020). Moreover, modern human hunter-gatherers show clear patterns of seasonal movement, with camps tending to be located near perennial water sources during the (late) dry season (e.g., Hawkes et al, 1997;Lee, 2013).…”
Section: Seasonality and Habitat Selection In The Oldowanmentioning
confidence: 99%